Tropical Tree Physiology Adaptations and Responses in a Changing Environment - Goldstein, Guillermo; Santiago, Louis S. (Tree Physiology ;, 2016)
This book presents the latest information on tropical tree physiology, making it a valuable research tool for a wide variety of researchers. It is also of general interest to ecologists (e.g. Ecological Society of America; > 3000 or 4000 members at annual meeting), physiologists (e.g. American Society of Plant Biologists; > 2,000 members at annual meeting), and tropical biologists (e.g. Association for Tropical Biology and Conservation, ATBC; > 500 members at annual meeting). (American Geophysical Union(AGU), > 20000 members at annual meeting). Since plant physiology is taught at every university that offers a life sciences, forestry or agricultural program, and physiology is a focus at research institutes and agencies worldwide, the book is a must-have for university and research institution libraries. .